FAKTOR PENYEBAB KERUSAKAN KAWASAN HUTAN TESSO NILO (STUDI PADA KANTOR BALAI TAMAN TESSO NILO) - Risdayanti, Tengku; Novarizal, Riky (SISI LAIN REALITA, 2022)
Forest was a green area in whic there is a lot of life both animal, plants, and human, presence of forest influence life around that forest be it ecologically, economic, and culturally.but what happened whem forest area having damaged and decreased quality owned then it will have an impact on the arrounding area. Destruction forest caused some factor natural and unnatural. This research studying damage factor happened in Tesso Nilo area district Pelalawan with qualitative and desriptive method, and routinity theory, whic shown that forrest damaged factor this area in the form of land fires, illegal logging, land clearing, elephant conflict.